2003
DOI: 10.1007/bf02708246
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature inhomogeneity on product profile of reactions occurring within zeolites

Abstract: In zeolites, diffusion is often accompanied by a reaction or sorption which in turn can induce temperature inhomogeneities. Monte Carlo simulations of Lennard-Jones atoms in zeolite NaCaA are reported for the presence of a hot zone presumed to be created by a reaction or chemi-or physi-sorption site. These simulations show that the presence of localized hot regions can alter both kinetic and transport properties such as diffusion. Further, we show that enhancement of diffusion constant is greater for systems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In general, low-temperature conditions were found to be helpful in inhibiting the chemisorption of propene on the highly acidic H-SAPO-34 catalysts, which can facilitate propene separation and allow for reliable monitoring of kinetic parameters. issues related to this product, including separation of propene from its mixture [7-9] and design of new catalytic materials to increase its production yield, stability, and recyclability [9][10][11][12][13][14][15][16]. To understand and cope with these issues, researchers are exploring different strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, low-temperature conditions were found to be helpful in inhibiting the chemisorption of propene on the highly acidic H-SAPO-34 catalysts, which can facilitate propene separation and allow for reliable monitoring of kinetic parameters. issues related to this product, including separation of propene from its mixture [7-9] and design of new catalytic materials to increase its production yield, stability, and recyclability [9][10][11][12][13][14][15][16]. To understand and cope with these issues, researchers are exploring different strategies.…”
mentioning
confidence: 99%
“…Such studies require experimental data free of any coupling or oligomerization reactions. Some literature have shown that propene reacts with zeolites [13,[17][18][19][20][21]. However, exact conditions of propene-zeolite reaction remain unclear, that is, whether propene reacts with every zeolite or whether there are exceptional circumstances is unknown.…”
mentioning
confidence: 99%